Associations of Husband Support with the Incidence of Post Partum Blues In the Working Area of Development Health Center and Tarogong Health Center Garut district - Liliek Pratiwi; Uus Husni Mahmud; Hutari Puji Astuti; Harnanik Nawangsari; Maharnani Tri Puspitasari; Winancy Winancy (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: Mothers are susceptible to experiencing postpartum blues syndrome during the postpartum period, or the period after giving birth. Rapid mood swings, feelings of sadness, worry, anxiety, and tiredness are signs of this syndrome, and mothers may feel more emotional and anxious, which can impact their mental health. Method: This type of research is quantitative analytical with a cross sectional approach. The population was postpartum mothers and the sample was 38 people with the inclusion criteria being postpartum mothers in the immediate postpartum to early postpartum categories who had previously had routine pregnancy checks in the Garut Regency Development Health Center working area. Data processing was carried out computerized with bivariate data analysis using the Chi Square statistical test. Results: The results of the study stated that 25 respondents had good husband support and 13 respondents had less husband support. Of the 38 respondents, 24 experienced postpartum blues . The results of this study stated that there was a link between husband's support and the incidence of postpartum blues , with a p value of 0.007. Conclusion: there is a connection between husband's support and the incidence of post partum blues, so that people can provide information to each other in preventing post partum blues . Health workers can also continue to be proactive in providing education to someone who plays the role of husband regarding the importance of maintaining the health of post partum mothers both physically and mentally for reproductive health and the health of mother and child .